Artistic interpretation of the epic creative image - Eshonkulov, Jabbor (International journal of linguistics, literature and culture, 2021)
Folklore is a unique art form. It differs from the written literature in its oral, traditional, varied, collective nature. That is, folk epics, which are an example of folklore, have many variants of their own. His text is not stable. These epics, sung by the bakhshis, differ from the epics, which are an example of written literature, in these aspects, that is, in their oral assimilation, oral performance, and oral heritage. These epics change in each performance as they are sung by the performer, the bakhshis. Because bakhshi is based on the law of live performance. Epic art, that is, the epics sung by the bakhshis to understand the essence of the content; it will be necessary to have a fuller understanding of the art of witchcraft. We can learn about the bakhshis from the epics they sang. Epics such as “Alpomish”, “Manas”, “Gorogly”, and the “Book of Dada Korkut” speak of the image of the bakhshi. This article deals with the artistic interpretation of the image of the epic creator in folk epics.